2007
DOI: 10.1101/gad.1505307
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary constraints on chaperone-mediated folding provide an antiviral approach refractory to development of drug resistance

Abstract: The genome diversity of RNA viruses allows for rapid adaptation to a wide variety of adverse conditions. Accordingly, viruses can escape inhibition by most antiviral compounds targeting either viral or host factors. Here we exploited the capacity of RNA viruses for rapid adaptation to explore the evolutionary constraints of chaperone-mediated protein folding. We hypothesized that inhibiting a host molecular chaperone required for folding of a viral protein would force the virus to evolve an alternate folding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
276
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(288 citation statements)
references
References 58 publications
11
276
0
1
Order By: Relevance
“…Inhibition of Hsp90 with small molecules such as geldanamycin and its derivatives has been shown to be antitumorigenic, and several of these compounds are currently in clinical trials (Chiosis et al, 2003;Neckers & Ivy, 2003;Solit et al, 2008;Workman, 2004). Hsp90 has also been implicated in other diseases including Alzheimers (Dickey et al, 2008), vascular disease (Shah et al, 1999), and viral diseses (Geller et al, 2007). In the case of RNA viruses, capsid proteins are clients of Hsp90, and Hsp90 inhibitors reduce viral replication because capsid proteins become misfolded and are targeted for degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of Hsp90 with small molecules such as geldanamycin and its derivatives has been shown to be antitumorigenic, and several of these compounds are currently in clinical trials (Chiosis et al, 2003;Neckers & Ivy, 2003;Solit et al, 2008;Workman, 2004). Hsp90 has also been implicated in other diseases including Alzheimers (Dickey et al, 2008), vascular disease (Shah et al, 1999), and viral diseses (Geller et al, 2007). In the case of RNA viruses, capsid proteins are clients of Hsp90, and Hsp90 inhibitors reduce viral replication because capsid proteins become misfolded and are targeted for degradation.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of RNA viruses, capsid proteins are clients of Hsp90, and Hsp90 inhibitors reduce viral replication because capsid proteins become misfolded and are targeted for degradation. The viruses also appear unable to bypass the requirement for Hsp90 through mutation making Hsp90 an attractive anti-viral target (Geller et al, 2007). Hsp90 also plays a role outside of protein folding by buffering phenotypic variation and allowing these variations to present themselves only under conditions of stress.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have provided a lot of information on the pharmacology of such inhibitors, and so far, they have revealed surprisingly few side effects. In addition, a recent study showed that Hsp90 inhibitors block infection of tissue culture cells by a wide panel of different viruses [10]. Not surprisingly, it has been suggested that the already available Hsp90 inhibitors could be further developed as anti-viral and anti-parasite agents.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of using antiviral compounds that target cellular factors is the limited emergence of resistant mutants. Mutants resistant to geldanamycin and PDTC were not isolated despite attempts (Geller et al, 2007;Krenn et al, 2009), although a mutant resistant to brefeldin A was isolated after five passages in cultured cells (Crotty et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Brefeldin A blocks membrane traffic between the cis-and trans-Golgi compartments by targeting a cellular guanine nucleotide-exchange factor, GBF1, and inhibits the replication of PV, but not encephalomyocarditis virus (EMCV) (Belov et al, 2008;Cuconati et al, 1998;Irurzun et al, 1992;Maynell et al, 1992). Geldanamycin targets Hsp90 and interferes with the folding of PV capsid, but not with RNA replication, probably in cooperation with Hsp70 (Geller et al, 2007;Macejak & Sarnow, 1992). Hippuristanol, a natural product of the coral Isis hippuis, inhibits RNA binding of eIF4A and delays the appearance of virus proteins in PV replication for 2 h (Bordeleau et al, 2006).…”
Section: Introductionmentioning
confidence: 99%